Prioridades en promoción de la salud según los profesionales de atención primaria: un estudio Delphi - Nebot, Manel (Aten Primaria, 2007)
OBJECTIVES: To find out the opinions of primary care professionals on prevention activities in clinical practice, as well as the perceived obstacles to carrying them out and ways of overcoming them. PARTICIPANTS: A total of 129 professionals participated, including primary care doctors, nurses, technicians, primary care service managers, and public health professionals. DESIGN: Delphi questionnaire sent by e-mail. SETTING: Primary care in Catalonia, Spain. MAIN MEASUREMENTS AND RESULTS: Two rounds were made with response rates of 48.9% and 67.4%, respectively. Convergence of over 40% was obtained in all the questions after the second round. The main problems for prevention in clinical practice were lack of time, lack of training and the attitudes of the professionals themselves towards prevention. To improve implementing prevention in the practice, the professionals pointed out, training in communication skills, advice methodology and the use of clinical practice guidelines. CONCLUSIONS: Health professionals pointed out some specific needs in training which could help to improve the inclusion of prevention activities. On the other hand, it was noted that the attitudes of the professionals themselves towards prevention need to be improved.